Glycemic effects following the consumption of mixed soy protein isolate and alginate beverages in healthy adultsElectronic supplementary information (ESI) available. See DOI: 10.1039/c8fo01627e - Huang, Zhaozhi; Wang, Yun; Shafer, Rebecca; Winn, Nathan C; Kanaley, Jill A; Vardhanabhuti, Bongkosh (2019)
This study examined whether the consumption of beverages containing mixed soy protein isolate (SPI) and fiber, alginate (ALG), would affect postprandial glucose and insulin responses or appetite in healthy adults. Following an overnight fast, twelve healthy subjects were asked to consume six standardized breakfast beverages in a randomized order: a 122 kcal sugar beverage (CONT), a 122 kcal sugar beverage with ALG, a 172 kcal sugar beverage with SPI at pH 7 (SPI-7) or 6 (SPI-6), and a 172 kcal sugar beverage with mixed SPI and alginate at pH 7 (SPI + ALG-7) or 6 (SPI + ALG-6). Subjects consumed one of the beverages at time 0. Blood samples were drawn at −15, 0, 15, 30, 45, 60, 90 and 120 min and questionnaires were completed immediately following the blood drawing at each time point. The results showed that, compared to CONT, the consumption of SPI-7, SPI-6, SPI + ALG-7 and SPI + ALG-6 significantly lowered ( P < 0.05) the peak plasma glucose concentration (33.4%, 36.3%, 53.2%, and 58.5%, respectively), 120 min incremental area under the curve (AUC), and peak insulin concentration. SPI + ALG-6 and SPI + ALG-7 exhibited a significant reduction in the peak glucose concentration compared to SPI without alginate ( P < 0.05). No significant effect on appetite was found in any conditions. Electrostatic interactions between the protein and alginate during digestion and formation of intragastric gel could play an important role in influencing the postprandial glucose response. This study indicates that the consumption of mixed SPI and ALG beverages was the most effective in attenuating the postprandial glycemic excursion in healthy adult subjects. Developing mixed soy protein and fiber beverages with reduced postprandial glucose response.